2004
DOI: 10.1590/s0100-879x2004001200001
|View full text |Cite
|
Sign up to set email alerts
|

A role for histone-like protein H1 (H-NS) in the regulation of hemolysin expression by Serratia marcescens

Abstract: The histone-like protein H1 (H-NS) is an abundant structural component of the bacterial nucleoid and influences many cellular processes including recombination, transcription and transposition. Mutations in the hns gene encoding H-NS are highly pleiotropic, affecting the expression of many unrelated genes. We have studied the role of H-NS on the regulation of hemolysin gene expression in Serratia marcescens. The Escherichia coli hns mutant carrying S. marcescens hemolysin genes on a plasmid constructed by liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The authors attributed this to the pleiotropic effects of the hns mutation. Other studies have reported H-NS to be involved in downregulation of toxins in different gramnegative bacteria including some proteins in the ToxR regulatory cascade in Vibrio cholerae (27), hemolysin in Serratia marcescens (9), and products of the spv virulence locus in Salmonella enterica serovar Typhimurium (28) and of two structural genes (mxiC and icsB) in Shigella flexneri (31).…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this to the pleiotropic effects of the hns mutation. Other studies have reported H-NS to be involved in downregulation of toxins in different gramnegative bacteria including some proteins in the ToxR regulatory cascade in Vibrio cholerae (27), hemolysin in Serratia marcescens (9), and products of the spv virulence locus in Salmonella enterica serovar Typhimurium (28) and of two structural genes (mxiC and icsB) in Shigella flexneri (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in hns gene have been shown to be involved in high level expression of cholera toxin in Vibrio cholerae (Nye et al 2000). More recently, H-NS has been shown to modulate expression of hemolysin, an important virulence factor of the opportunistic pathogen Serratia marcescens (Franzon & Santos 2004). In addition, deletion of the hns gene has been shown to confer drug resistance to E. coli by repressing multidrug exporter genes (Nishino & Yamaguchi 2004).…”
Section: Finding and Validating New Drug Targets In M Tuberculosismentioning
confidence: 99%
“…The best studied NAPs are Fis (factor for inversion stimulation), H-NS (histone-like nucleoid structuring), HU (heat unstable) and IHF (integration host factor), although the existence of other similar proteins is becoming increasingly apparent (Luijsterburg et al, 2008). Their structural and functional properties have been related to chromatin compaction (by bending, bridging and wrapping DNA) and global transcriptional regulation of several genes, including virulence genes of bacterial pathogens (Beloin & Dorman, 2003;Berlutti et al, 1998;Falconi et al, 2001;Franzon & Santos, 2004; Harrison et al, 1994; Mangan et al, 2006;Nye et al, 2000;Schechter et al, 2003;Stonehouse et al, 2008; Wilson et al, 2001). Most of these proteins have been reported to bind to non-specific DNA sequences (Bailly et al, 1995;Krylov et al, 2001;Yamada et al, 1991), to exhibit low sequence or structural conservation (Luijsterburg et al, 2008), and to induce DNA bending and other alterations (Dhavan et al, 2002;Koh et al, 2008; Schneider et al, 2001;Spurio et al, 1997;Swinger & Rice, 2004).…”
Section: Introductionmentioning
confidence: 99%